1998
DOI: 10.1258/0956462981921675
|View full text |Cite
|
Sign up to set email alerts
|

The management of Chlamydia trachomatis genital infection in genitourinary medicine clinics in the Wessex region

Abstract: The management of cases of Chlamydia trachomatis genital infection diagnosed in clinics in Wessex in the last quarter of 1996 was surveyed, and the results compared with those obtained in the national gonorrhoea audit. Treatment regimens were extremely varied both between and within clinics. Overall, 71% of patients saw a health adviser, 74% returned for follow-up, and 96% of these were cured. Compared with the national gonorrhoea audit, fewer contacts were reported (1.2 vs 1.5), but more contacts were seen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Fewer cases (39%) had follow up in clinics in this audit when compared with the 2004 Audit where 50% had clinic follow up. There is limited previous reporting of follow up of chlamydial cases but two regional audits have shown similar overall follow-up rates of 74 6 and 70%, 7 both through clinic reattendance. More telephone follow up is consistent with the National Guideline quoted evidence-base that follow up by 'phone "may be more efficacious and cost effective than by reattendance."…”
Section: Discussionmentioning
confidence: 99%
“…Fewer cases (39%) had follow up in clinics in this audit when compared with the 2004 Audit where 50% had clinic follow up. There is limited previous reporting of follow up of chlamydial cases but two regional audits have shown similar overall follow-up rates of 74 6 and 70%, 7 both through clinic reattendance. More telephone follow up is consistent with the National Guideline quoted evidence-base that follow up by 'phone "may be more efficacious and cost effective than by reattendance."…”
Section: Discussionmentioning
confidence: 99%
“…Case management and partner notification outcomes were not influenced by age, gender or sexuality, but were significantly associated with ethnicity (outcomes better in whites). Previous audits 11,12 of the management of CT have shown that the ratio of index cases to contacts was 1 to 1.2. In this national audit, the ratio was 1 to 1.5 (similar to the national gonorrhoea audit 18 ), which is in keeping with changes in sexual behaviour 19 and increasing incidence of CT. 1…”
Section: Discussionmentioning
confidence: 98%
“…Previous audits of the management of chlamydia have been limited to single clinics, multi-districts and regions. [8][9][10][11][12][13][14] This paper presents the findings of the first national audit of the management of genital chlamydia by NCCG doctors working in GU medicine clinics in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Both systems rely on a great deal of good will and energy from their contributors, with CDC providing a stimulating and enjoyable forum to debate developments in the evidence, and to guarantee that regular reviews will take place. The CEG guidelines are known to be used in audit 6,7 and influence other sources of guidance to UK health practitioners and patients; market research shows that the CDC guidelines are widely used. It would be helpful for both groups to gain more evidence on just how much guidelines influence what practitioners actually do.…”
Section: Discussionmentioning
confidence: 99%